2013
DOI: 10.4236/ns.2013.55073
|View full text |Cite
|
Sign up to set email alerts
|

Metals toxicity and its bioaccumulation in purslane seedlings grown in controlled environment

Abstract: We aimed to find the toxicological impacts of Cd, Pb and Zn in single dozes and in combinations on Purslane (Portulaca oleracea) seedling. The Pursolane seedlings  grown in pots in a green house were treated with different soil treatments spiked (mg/kg) with Pb (300, 400 and 500), Cd (0.5, 1 and 1.5), and Zn (250, 500, 700) alone and then in specified combinations/concentrations i.e., Cd/Pb (0.5/300, 1/400, 1.5/500), Cd/Zn (0.5/250, 1/500, 1.5/700) and Pb/Zn (300/250, 400/500, 500/ 700). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
7
20
0
Order By: Relevance
“…Similarly, Ni and Cr higher concentrations in plant species may lead to phytotoxicity. Enrichment of these metals in wild flora could be a serious threat to community of the area [1, 7, 9, 10]. However, Mewis et al [42] reported that for detoxification of metal stress and competition the accumulator plant species activate the defense mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Ni and Cr higher concentrations in plant species may lead to phytotoxicity. Enrichment of these metals in wild flora could be a serious threat to community of the area [1, 7, 9, 10]. However, Mewis et al [42] reported that for detoxification of metal stress and competition the accumulator plant species activate the defense mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…These multifold higher concentrations of metals can be attributed to the mafic and ultramafic terrain and chromite mining in the area [1, 7, 9, 10]. Inter-relationship of physiochemical parameters in soil of the study area is summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals such as Cr, Ni, Fe, Mn, Cu and Zn showed significantly (p < 0.01) higher concentrations among the selected heavy metals in Mohmand Agency, Shangla District and Malakand Agency as compared to reference site Table 2. This multifold higher concentration can be attributed to mafic and ultramafic rocks and chromites min- ing in the study area (Shah et al 2010;Yang et al 2011;Naz et al 2013). The inter-elemental correlation in soil sample showed that some pairs of heavy metals have strong significant correlation like Cr-Ni (r = 0.784), Cr-Co (r = 0.589), Cr-Fe(r = 0.432), Ni-Co (r = 0.391), Ni-Fe (r = 0.317) and Co-Fe (r = 0.603) (Table 5).…”
Section: Inter-elemental Correlations In Plants and Soilmentioning
confidence: 95%
“…These results were confirmed by Somova and Pechurkin who showed a high tolerance of plants to zinc salts (Somova and Pechurkin 2009). In non-tolerant plants, Zn toxicity is apparent in soils with high Zn content which could affect inhibition of root elongation and chlorosis of young leaves (Nicholson et al 1997, González and Lobo 2013, Naz et al 2013. Though Zn was once not considered to be highly toxic, phytotoxicity of zinc is usually reported in acid and heavily sludged soils.…”
Section: Phytotoxicity Effect Of Hmmentioning
confidence: 99%